The design of the digital transformation in Vocational Education and Training – new demands to company training staff - Härtel, Michael [Verfasser] (My University, 2022)
„In-company trainers are not only experts in their respective profession but also play a major role in the socialisation of young persons and their integration into an increasingly digitalized work environment. Digitalisation requires trainers and teachers in Vocational Education and Training to adopt new media-pedagogical competencies consisting of media-didactic, media education, and media integration skills. In order to support training personnel in shaping the digital transformation, BIBB has developed a seminar concept to promote the media and IT competence of in-company training staff. “ (author’s abstract; BIBB-Doku)
Keywords: P 3.2.1 Ausbilder; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; 370; Berufsausbildung; Digitalisierung; Ausbilder; Medienkompetenz; Digitalkompetenz; Qualifizierung; Unterrichtskonzept